2002
DOI: 10.1143/jjap.41.5654
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nanoparticles Formed during Pulsed Laser Ablation of SrBi2Ta2O9

Abstract: The technical problem of deriving the full Green functions of the elementary pion fields of the nonlinear sigma model in terms of ancestor amplitudes involving only the flat connection and the nonlinear sigma model constraint is a very complex task. In this paper we solve this problem by integrating, order by order in the perturbative loop expansion, the local functional equation derived from the invariance of the SU(2) Haar measure under local left multiplication. This yields the perturbative definition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…17) It is commonly observed that nanoparticles fabricated by laser ablation have low crystallinity owing to a very short residence time, as short as approximately 0.06 s for nanoparticles crystallized in an electric furnace. 21) Although this residence time is of an order similar to that for the plasma CVD process, the nanoparticles undergo significantly higher temperatures, which allows greater crystallization in the case of plasma CVD. As a result, the present nanoparticles have lower crystallinity, even after the post-annealing process under the same conditions using the same apparatus, than our former films prepared by plasma CVD.…”
Section: Size Dependence Of Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17) It is commonly observed that nanoparticles fabricated by laser ablation have low crystallinity owing to a very short residence time, as short as approximately 0.06 s for nanoparticles crystallized in an electric furnace. 21) Although this residence time is of an order similar to that for the plasma CVD process, the nanoparticles undergo significantly higher temperatures, which allows greater crystallization in the case of plasma CVD. As a result, the present nanoparticles have lower crystallinity, even after the post-annealing process under the same conditions using the same apparatus, than our former films prepared by plasma CVD.…”
Section: Size Dependence Of Dielectric Propertiesmentioning
confidence: 99%
“…Recent studies have particularly been focused on size regions smaller than 150 nm. [17][18][19][20] The laser ablation method is known to be effective for the preparation of ferroelectric nanoparticles such as SrBi 2 Ta 2 O 9 (SBT) 21) and PbZr x Ti 1Àx O 3 (PZT) 22) with a particle size of approximately 10 nm. These nanoparticles can be deposited on a substrate, which enables the preparation of films with ferroelectric fine grains.…”
Section: Introductionmentioning
confidence: 99%